Caribbean-wide, long-term study of seagrass beds reveals local variations, shifts in community structure and occasional collapse. - Brigitta I van Tussenbroek; Jorge Cortés; Rachel Collin; Ana C Fonseca; Peter M H Gayle; Hector M Guzmán; Gabriel E Jácome; Rahanna Juman; Karen H Koltes; Hazel A Oxenford; Alberto Rodríguez-Ramirez; Jimena Samper-Villarreal; et al. (PLoS ONE, 2014)
The CARICOMP monitoring network gathered standardized data from 52 seagrass sampling stations at 22 sites (mostly Thalassia testudinum-dominated beds in reef systems) across the Wider Caribbean twice a year over the period 1993 to 2007 (and in some cases up to 2012). Wide variations in community total biomass (285 to >2000 g dry m(-2)) and annual foliar productivity of the dominant seagrass T. testudinum (<200 and >2000 g dry m(-2)) were found among sites. Solar-cycle related intra-annual variations in T. testudinum leaf productivity were detected at latitudes > 16°N. Hurricanes had little to no long-term effects on these well-developed seagrass communities, except for 1 station, where the vegetation was lost by burial below ∼1 m sand. At two sites (5 stations), the seagrass beds collapsed due to excessive grazing by turtles or sea-urchins (the latter in combination with human impact and storms). The low-cost methods of this regional-scale monitoring program were sufficient to detect long-term shifts in the communities, and fifteen (43%) out of 35 long-term monitoring stations (at 17 sites) showed trends in seagrass communities consistent with expected changes under environmental deterioration.